In Search of a Universal Landmark of Hermeneutic Reflection - Vardidze, Vaja (Verbum Vitae, 2025)
The aim of the present article is to identify a universal landmark of hermeneutics in order to discern what is involved in the act of cognition and the object towards which the process of understanding is directed. The focus is placed on a paradigmatic shift from the horizon of dialogue between inner and outer speech to a perspective of freedom, which ultimately confers meaning upon the act of dialogue itself. In this context, reference is made to Hermann Krings’ transcendental analysis of freedom, which does not provide a direct answer to the hermeneutical question, but rather thematizes the preconditions for the realization of freedom. This thematization elucidates the substantive dimension of cognition, engages its point of origin and its teleological orientation, and substantiates the phenomenological perspective. However, in order to ensure that transcendental analysis is not construed as an absolutist claim regarding the determination of consciousness, the present article also points to the need for defining the status of the hermeneutical process itself. The process of transcendental analyses presupposes factuality, revisits the historical-critical method, and aims to “regulate” the inherent dynamics and laws of understanding. Such an approach gestures toward the horizon of the possibility of understanding, which, although shaped by a regulative concept (a worldly mediation) and situated within a framework of epistemic reference or a particular system of thought—may also be determined by the creative act of the Absolute. As such, this act transcends the existing epistemic frameworks and cognitive systems, thereby opening a theological perspective that does not negate rational categories but rather integrates them into the quest for an order oriented toward the Absolute.